2019
DOI: 10.14245/ns.1836296.148
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Multifocal Spine Infections Involving the Cervical and Thoracic Regions: A Case for Imaging the Entire Spine

Abstract: Objective: Pyogenic spinal infections account for 2%-4% of orthopaedic infections. They are often difficult to diagnose, resulting in a delay in diagnosis. Risk factors for orthopaedic and spinal infection are well-documented in the literature, yet there is a paucity of studies examining risk factors specifically for multifocal spinal infections. The objective of this study was to identify predictors of multifocal spinal infections in comparison to unifocal spinal infections. Methods: The medical records, imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…This case illustrates a 60-year-old man with gingivitis and immunocompromise related to diabetes who developed multi-focal cervical and lumbar pyogenic infection (ie, paraspinal, psoas, and epidural abscesses) shortly after COVID-19 illness. Accordingly, this case reinforces previous associations between immunocompromise and opportunistic pyogenic spinal infection [ 5 ], and adds to the growing literature showing that COVID-19 illness is another potential risk factor for these types of infections [ 11 17 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This case illustrates a 60-year-old man with gingivitis and immunocompromise related to diabetes who developed multi-focal cervical and lumbar pyogenic infection (ie, paraspinal, psoas, and epidural abscesses) shortly after COVID-19 illness. Accordingly, this case reinforces previous associations between immunocompromise and opportunistic pyogenic spinal infection [ 5 ], and adds to the growing literature showing that COVID-19 illness is another potential risk factor for these types of infections [ 11 17 ].…”
Section: Discussionsupporting
confidence: 85%
“…Well-described risk factors for pyogenic spinal infection include immunocompromise, diabetes mellitus, substance abuse, chronic infection such as HIV, malnutrition, long-term systemic steroid use, and spine surgery [ 1 , 4 ]. Pyogenic spinal infections are most common in the lumbar region [ 3 ], and are multifocal in 35% of cases, affecting more than 1 spinal region [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The common finding seen in MRI was epidural empyema with predominantly lumbar spine involvement. In a recent study examining the spinal involvement in PSI, multifocal involvement was found to be common (35%) [23]. This highlights the need to image the entire spine, especially prior to any surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Elucidation of these differences may provide clarity and standardisation in the screening for multifocal infections. Our previous study had investigated those differences and found that patients surgically treated for cervical or thoracic spinal infections had a high rate of multifocal spinal infections (71 % and 83 %, respectively) (Balcescu et al, 2019). However, the power of our study was small due to the sole inclusion of patients who were operated on at a single institution over the course of 6 years.…”
Section: Introductionmentioning
confidence: 86%
“…Therefore, it is imperative to promptly identify all involved regions of the spine so that the appropriate treatment can be administered. Our previous single-institution retrospective study found an incidence of 35 % for multifocal infections in the patients surgically treated for non-tuberculous pyogenic spinal infections (Balcescu et al, 2019). Other studies have reported incidences of multifocal spinal infection ranging from 4 % to 30 % (Ledermann et al, 2003;Mann et al, 2004;Ziu et al, 2014;Cox et al, 2018).…”
Section: Introductionmentioning
confidence: 89%